Systems Toxicology and the Chemical Effects in Biological Systems (CEBS) Knowledge Base - Waters, Michael; Boorman, Gary; Bushel, Pierre; Cunningham, Michael; Irwin, Rick; Merrick, Alex; Olden, Kenneth; Paules, Richard; Selkirk, James; Stasiewicz, Stanley; Weis, Brenda; van Houten, Ben; et al. (Environmental health perspectives, 2003)
The National Center for Toxicogenomics is developing the first public toxicogenomics knowledge base that combines molecular expression data sets from transcriptomics, proteomics, metabonomics, and conventional toxicology with metabolic, toxicological pathway, and gene regulatory network information relevant to environmental toxicology and human disease. It is called the Chemical Effects in Biological Systems (CEBS) knowledge base and is designed to meet the information needs of "systems toxicology," involving the study of perturbation by chemicals and stressors, monitoring changes in molecular expression and conventional toxicological parameters, and iteratively integrating biological response data to describe the functioning organism. Based upon functional genomics approaches used successfully in analyzing yeast gene expression data sets, relational and descriptive compendia will be assembled for toxicologically important genes, groups of genes, single nucleotide polymorphisms (SNPs), and mutant and knockout phenotypes. CEBS data sets will be fully documented in the experimental protocol and therefore searchable by compound, structure, toxicity end point, pathology end point, gene, gene group, SNP, pathway, and network as a function of dose, time, and the phenotype of the target tissue. A knowledge base is being developed by assimilating toxicological, biological, and chemical information from multiple public domain databases and by progressively refining that information about gene, protein, and metabolite expression for classes of chemicals and their biological effects in various species. By analogy to the GenBank database for genome sequences, researchers will globally query (or BLAST) CEBS using a transcriptome of a tissue of interest (or a list of outliers) to have the knowledge base return information on genes, groups of genes, metabolic and toxicological pathways, and contextually associated phenotypic information for compounds that display similar response profiles. With high-quality data content, CEBS will ultimately become a resource to support hypothesis-driven and discovery research that contributes effectively to drug safety and the improvement of risk assessments for chemicals in the environment. The CEBS development effort will span a decade or more.